Synchrotron ultraviolet microspectroscopy on rat cortical bone: involvement of tyrosine and tryptophan in the osteocyte and its environment. - Stéphane Pallu; Gael Y Rochefort; Christelle Jaffre; Matthieu Refregiers; Delphine B Maurel; Delphine Benaitreau; Eric Lespessailles; Frédéric Jamme; Christine Chappard; Claude-Laurent Benhamou (PLoS ONE, 2012)
Alcohol induced osteoporosis is characterized by a bone mass decrease and microarchitecture alterations. Having observed an excess in osteocyte apoptosis, we aimed to assess the bone tissue biochemistry, particularly in the osteocyte and its environment. For this purpose, we used a model of alcohol induced osteoporosis in rats. Bone sections of cortical bone were investigated using synchrotron UV-microspectrofluorescence at subcellular resolution. We show that bone present three fluorescence peaks at 305, 333 and 385 nm, respectively corresponding to tyrosine, tryptophan and collagen. We have determined that tyrosine/collagen and tryptophan/collagen ratios were higher in the strong alcohol consumption group. Tryptophan is related to the serotonin metabolism involved in bone formation, while tyrosine is involved in the activity of tyrosine kinases and phosphatases in osteocytes. Our experiment represents the first combined synchrotron UV microspectroscopy analysis of bone tissue with a quantitative biochemical characterization in the osteocyte and surrounding matrix performed separately.